The Effect of Adding an EM-4 Activator Mixture to Tofu Dregs on Increasing the Biomass of Silk Worms (Tubifex sp.) - Dubel Pituan Simamora; Suri Purnama Febri; Siti Komariyah; Pebry Aisyah Putri Batubara (Jurnal Ilmiah Samudra Akuatika, 2025)
Silkworms (Tubifex sp.) is an important natural feed in aquaculture as a natural feed that can accelerate fish growth, particularly during the hatchery phase. This study aimed to analyze the effect of EM-4 activator supplementation in tofu waste on the biomass increase of Tubifex sp. The research was conducted using an experimental method with a Completely Randomized Design consisting of five treatments and three replications. The treatments were P1 (EM-4 0 ml/10 g tofu waste), P2 (EM-4 1 ml/10 g tofu waste), P3 (EM-4 2 ml/10 g tofu waste), P4 (EM-4 3 ml/10 g tofu waste), and P5 (EM-4 4 ml/10 g tofu waste). The results showed that EM-4 application in tofu waste had a significant effect on increasing the biomass of Tubifex sp. The highest biomass was obtained in treatment P5, reaching 10.28 ± 0.80. These findings indicate that tofu waste enriched with EM-4 has strong potential as an effective, economical, and environmentally friendly culture medium for Tubifex sp., supporting the sustainable availability of natural feed for fish hatchery operations.